Hubungan Dua Arah Antara Gastroesophageal Reflux Disease dengan Gangguan Tidur - Rahmadani, Tiara Sekar; Graharti, Risti; Septa, Tendry (Medula, 2026)
Gastroesophageal Reflux Disease (GERD) is a common chronic gastrointestinal disorder characterized by recurrent reflux of gastric contents into the esophagus, causing symptoms such as heartburn, chest pain, chronic cough, and nocturnal discomfort. The global prevalence of GERD continues to increase and is closely associated with lifestyle factors, including high body mass index, excessive caffeine and alcohol consumption, psychological stress, and poor sleep patterns. In Asia, GERD prevalence has risen markedly over the past two decades, with intercountry differences reflecting variations in socioeconomic status and health behaviors. Nocturnal GERD symptoms frequently disrupt sleep quality, most commonly through insomnia and obstructive sleep apnea (OSA). These sleep disorders can physiologically worsen reflux by altering intrathoracic pressure and reducing lower esophageal sphincter tone. Recent evidence suggests a bidirectional relationship between GERD and sleep disorders, in which nocturnal reflux leads to sleep fragmentation, while sleep disturbances increase the frequency and severity of reflux episodes. Other contributing factors include stress, high-fat dietary intake, impaired esophageal motility, and reduced nocturnal acid clearance. This literature review summarizes current evidence regarding the physiological links between GERD and sleep disorders, associated risk factors, and available management strategies. Therapeutic approaches include pharmacological treatments such as proton pump inhibitors (PPIs) and potassium-competitive acid blockers (P-CABs), along with non-pharmacological interventions, including sleeping in the left lateral position, which has been shown to reduce nocturnal reflux events. This review highlights the importance of a multidisciplinary management approach and the need for further research to improve GERD symptoms and sleep quality.